Urothelial Carcinoma of the Urinary Bladder in Young Adults: Presentation, Clinical behavior and Outcome. (22nd November 2011) - Nomikos, Michael; Pappas, Athanasios; Kopaka, Maria-Emmanouela; Tzoulakis, Stavros; Volonakis, Ioannis; Stavrakakis, Georgios; Avgenakis, Georgios; Anezinis, Ploutarchos
Abstract : Introduction. There is not much evidence regarding clinical behavior of bladder cancer in younger patients. We evaluated clinical characteristics, tumor recurrence and progression in patients younger than 40 years old with urothelial bladder carcinoma. Methods. We retrospectively reviewed the medical records of 31 patients less than 40 years old who were firstly managed with bladder urothelial carcinoma in our department. Data were analysed with the Chi-square test. Results. Mean age was 31.7 years. Mean followup was 38.52 months (11–72 months). Nineteen (61%) patients were diagnosed with GII and 2 (6%) patients with GIII disease. Five (16%) patients presented with T1 disease. Three (9%) patients with invasive disease underwent cystectomy and adjuvant chemotherapy and one developed metastatic disease. Ten (32%) patients recurred during followup with a disease free recurrence rate of 65% the first 2 years after surgery. From those, 1 patient progressed to higher stage and three to higher grade disease. No patient died during followup. Conclusions. Bladder urothelial carcinoma in patients younger than 40 years is usually low stage and low grade. Management of these patients should be according to clinical characteristics and no different from older patients with the same disease.